2013
DOI: 10.1371/journal.pbio.1001601
|View full text |Cite
|
Sign up to set email alerts
|

Single Cell Visualization of Yeast Gene Expression Shows Correlation of Epigenetic Switching between Multiple Heterochromatic Regions through Multiple Generations

Abstract: A single-cell method allows the assessment of relationships between the dynamic epigenetic behavior of yeast heterochromatin boundaries over multiple generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…Colonies of yeast that are ade1 Δ are a dark red colour; reintroduction of functional Ade1 protein restores the wild type white coloration in a dose-dependent manner. Such differences in colony colour and ability to grown on adenine dropout media (SD-Ade) have been utilized to differentiate strains of yeast prions37, assess mitotic stability38 and monitor gene expression39.…”
Section: Resultsmentioning
confidence: 99%
“…Colonies of yeast that are ade1 Δ are a dark red colour; reintroduction of functional Ade1 protein restores the wild type white coloration in a dose-dependent manner. Such differences in colony colour and ability to grown on adenine dropout media (SD-Ade) have been utilized to differentiate strains of yeast prions37, assess mitotic stability38 and monitor gene expression39.…”
Section: Resultsmentioning
confidence: 99%
“…This question has been addressed with pairs of fluorescent reporter genes integrated at separate silenced locations. In one study, correlated switches in expression state were observed in cell lineages when the genes were placed at the edges of the silent chromatin domains at HMR and HML (Mano et al 2013). These results indicate that inheritance of silent chromatin is influenced by a property that is generic to the cell and not specific to the locus.…”
Section: Variegated Expression and Inheritancementioning
confidence: 98%
“…When reporters were placed at an artificial telomere or beyond the silencers at HMR expression, their expression was variegated (Gottschling et al 1990;Simms et al 2008;Mano et al 2013). In the case of the ADE2 reporter, silenced cells acquired a red pigment whereas genetically identical, nonsilent cells remained white.…”
Section: Variegated Expression and Inheritancementioning
confidence: 99%
“…For example, loss of the euchromatin-associated bromodomain protein Bdf1 or histone variant H2A.Z results in expanded heterochromatin regions [98, 99]. As a result of such competition, negotiable borders are associated with frequent changes of epigenetic states [100]. The classical example of PEV in Drosophila , where white is silenced in a portion of progenitor cells during early development, also suggests that heterochromatin spreads over varying distances rather than being constrained to a defined location.…”
Section: Negotiable Bordersmentioning
confidence: 99%